Implementation, Advantages and Barriers and Legal Protection Against the Use of Electronic Signatures - Muhammad Nova Haikal; Siti Mahmudah (International Journal Labs, 2024)
The Government has promulgated Law of the Republic of Indonesia Number 11 of 2008 concerning Electronic Information and Transactions as first amended by Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions and amended again by Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions; and The government has also made derivative regulations in the form of Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions. Currently, the Government through the Ministry of Communication and Information Technology has also granted permission to agencies or legal entities authorized as Electronic Certification Providers (PSrE) that provide electronic certificate and electronic signature services. However, the fact is that today people still rarely or do not know how to use electronic signatures or electronic transactions in every agreement. Often people also do not know about the difference between electronic signatures or signature scans. People today also still doubt the legal consequences and legal risks that occur if electronic transactions and/or electronic documents are signed through electronic signatures. With the existing facilities and infrastructure made by the current government, people should be able to use electronic signatures in electronic transactions, both in buying and selling transactions, accounts receivable or the implementation of other agreements that are often carried out in the community. Therefore, this study aims to discuss and elaborate the implementation of provisions regarding the use of Electronic Signatures in electronic transactions and electronic contracts and also to provide an understanding of legal protection to facilitate and convince the public to be able to carry out transactions and agreements electronically.